2023
DOI: 10.3390/ijms24021752
|View full text |Cite
|
Sign up to set email alerts
|

Treg Therapy for the Induction of Immune Tolerance in Transplantation—Not Lost in Translation?

Abstract: The clinical success of solid organ transplantation is still limited by the insufficiency of immunosuppressive regimens to control chronic rejection and late graft loss. Moreover, serious side effects caused by chronic immunosuppressive treatment increase morbidity and mortality in transplant patients. Regulatory T cells (Tregs) have proven to be efficient in the induction of allograft tolerance and prolongation of graft survival in numerous preclinical models, and treatment has now moved to the clinics. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Treg is a specialized subset of CD4 T cells characterized by the high expression of FoxP3 and interleukin-2 (IL-2) receptor CD25, and low expression of IL-7 receptor CD127[ 19 ]. Based on developmental origins, CD4+ Tregs could be divided into thymic Tregs (tTregs) and peripheral Tregs (pTregs).…”
Section: Tregs and The Induction Of Tolerancementioning
confidence: 99%
“…Treg is a specialized subset of CD4 T cells characterized by the high expression of FoxP3 and interleukin-2 (IL-2) receptor CD25, and low expression of IL-7 receptor CD127[ 19 ]. Based on developmental origins, CD4+ Tregs could be divided into thymic Tregs (tTregs) and peripheral Tregs (pTregs).…”
Section: Tregs and The Induction Of Tolerancementioning
confidence: 99%
“…However, given the bystander properties of Tregs and the recognition that organ-specific Tregs play a critical role in controlling autoimmunity in the local tissue environment, it was hypothesized that Tregs with single-antigen specificities might have an increased specific activity and a greater safety profile. In fact, data in multiple autoimmune ( 43 ) and transplant settings ( 44 ) showed that Treg cells expressing a single T cell receptor (TCR) suppressed autoreactive, multi-specific Teff cells and led to long-term tolerance. In fact, preliminary data in humans suggest that alloantigen-specific Treg cells can be effective in the transplantation setting ( 45 ).…”
Section: The Tolerogenic Potential Of Treg Therapiesmentioning
confidence: 99%
“…Tregs are regulatory T cells capable of secreting cytokines such as IL‐4, IL‐10, and TGFβ, which play an important role in immune homeostasis and induction of immune tolerance 55 . HLA‐G is an important factor to prevent the fetus from being rejected by the mother's immune system.…”
Section: Mscs and The Immunogenicitymentioning
confidence: 99%
“…Tregs are regulatory T cells capable of secreting cytokines such as IL-4, IL-10, and TGFβ, which play an important role in immune homeostasis and induction of immune tolerance. 55 HLA-G is an important factor to prevent the fetus from being rejected by the mother's immune system. MSCs participate in inducing the proliferation of Tregs by secreting HLA-G. 56 MSCs are also believed to control immune tolerance by secreting HLA-G-5 and -7 isotypes, thereby affecting allograft tolerance.…”
Section: Tregsmentioning
confidence: 99%